'It's good to talk' – auditing the effect of a consultant-led phone advice service within the emergency department. (24th May 2012) - Fish, R; Christian, W; Roberts, Z; Seckley, J
Abstract : Introduction: With increasing pressures on acute paediatric services, the need for providing more focussed, increasingly consultant delivered services is clear. The Children's Emergency Department sees a significant year-on-year increase in attendances, many of which can be inappropriate or unnecessary, so can we alleviate some of this pressure whilst supporting our community-based colleagues? Methods/Design: A one-month pilot study was undertaken between April and May of this year, looking at all phone referrals to the department. Either the Consultant or most experienced trainee in the department received the calls. The results were then re-audited in June of this year. Details documented included: Patient's name, age and date of birth; Referrer; Brief history /examination findings; Advice given; Outcome; Results: A total of 268 phone referrals were received: 85% from GPs, 2% from other hospitals; 9% from WIC; 4% from 'others'. Calls taken were roughly evenly split between Consultants and Middle Grades. Following discussion, 74% were seen in ED, 19% given advice, 3% had escalated management and 4% were redirected to outpatients. A survey was also sent to GPs who had made referrals in this manner to gain their views and experiences of the service. For the month of June, results showed an increase in the number of calls (350) with 71% coming from GPs. This also showed a peak in the number of calls between 11-12 and at 1700 hours, reflecting the college recommendations that a consultant should be present at times of peak activity. Conclusion: The system has so far proved worthwhile with almost a quarter of calls preventing attendance on the basis of management advice or a more appropriate disposal option. Feedback is needed from a greater number of health professionals, as is, assessing its sustainability. The system appears a positive clinical governance and medico legal measure, providing clear documentation and a paper trail that can be referred to should there be concerns. There is also potential, in the future, to charge for such a service, helping gain revenue for the department.